2011
DOI: 10.1111/j.1551-2916.2010.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ni-Doped SiC Nanopowders and their Dielectric Properties

Abstract: Nanopowders of nickel‐doped β‐silicon carbide (β‐SiC) with improved dielectric properties (compared with pure β‐SiC) were successfully produced using the mechanically activated self‐propagating high‐temperature synthesis method in an argon (Ar) atmosphere. The molar substitution of nickel (Ni) for silicon (Si) was 1%, 3%, and 5%. Powders of poly(tetrafluoroethylene) and ammonium chloride (NH4Cl) were used to promote the combustion reaction. The experimental results indicated an active role of Ni in the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Dielectric, electromagnetic absorption and interference shielding properties of multi-phase composites, such as SiC/CNTs [8], carbon black/SiC [9], Si 3 N 4 -SiC composite ceramics [10], porous yttria-stabilized zirconia (YSZ)/silicon carbide composites [11] and three-phase composites comprising poly(vinylidene fluoride)(PVDF), barium titanate (BT) nanoparticles and β-silicon carbide (β-SiC) whiskers [12], are investigated. Improving microwave loss factor and microwave-absorption performance have also been observed in the doped SiC with other elements, such as B [13,14], N [15][16][17], Al [18][19][20][21], Ni [22], and Al-N [23]. Surface modification is another effective approach to enhance microwave loss factor and microwave-absorption behavior [24,25].…”
Section: Introductionmentioning
confidence: 92%
“…Dielectric, electromagnetic absorption and interference shielding properties of multi-phase composites, such as SiC/CNTs [8], carbon black/SiC [9], Si 3 N 4 -SiC composite ceramics [10], porous yttria-stabilized zirconia (YSZ)/silicon carbide composites [11] and three-phase composites comprising poly(vinylidene fluoride)(PVDF), barium titanate (BT) nanoparticles and β-silicon carbide (β-SiC) whiskers [12], are investigated. Improving microwave loss factor and microwave-absorption performance have also been observed in the doped SiC with other elements, such as B [13,14], N [15][16][17], Al [18][19][20][21], Ni [22], and Al-N [23]. Surface modification is another effective approach to enhance microwave loss factor and microwave-absorption behavior [24,25].…”
Section: Introductionmentioning
confidence: 92%
“…It was reported that doping of SiC with N (p-type) or B (p-type) or mental (Ti, Ni and Al) had better microwave dielectric loss in the X-band than that obtained pure SiC [8][9][10][11][12]. Silicon carbonitride (Si-C-N) ceramic is a promising material [13] for its attractive properties, such as corrosion resistance, high temperature oxidation resistance, hardness and wide band gap [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…To prepare elongated b-Si 3 N 4 particles, we used a novel gel-cast-foam-assisted CS method. This method is based on conventional combustion synthesis and developed with the favor of gel-casting-foam method [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%